2012
DOI: 10.1080/00036846.2011.560110
|View full text |Cite
|
Sign up to set email alerts
|

Environmental policy stringency and technological innovation: evidence from survey data and patent counts

Abstract: This paper uses patent data to examine the impact of public environmental policy on innovations in environment-related technology. The analysis is conducted using data on an unbalanced panel of 77 countries between 2001 and 2007, drawing upon data obtained from the EPO World Patent Statistical (PATSTAT) database and the World Economic Forum's "Executive Opinion Survey". The results support our hypotheses concerning the positive role of both general innovative capacity and environmental policy stringency on env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
125
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(142 citation statements)
references
References 33 publications
(35 reference statements)
6
125
0
6
Order By: Relevance
“…In this way the firm pays the same marginal price for each unit of pollution. While Johnstone (2005) argues that the choice of regulatory strategy should be flexible and be able to adapt to changing market conditions, Johnstone, Haščič and Kalamova (2010) find evidence that less rigid innovation regulations based on taxes and tradable permits are more effective at inducing eco-innovation than strict performance standards or technology based controls. They also find evidence that any policy that sets a strict price for polluting incentivises firms to search for ways to avoid these costs and they find that any increase in that price induces further innovation (especially air, water and waste management innovation).…”
Section: Regulation As An Eco-innovation Drivermentioning
confidence: 97%
See 1 more Smart Citation
“…In this way the firm pays the same marginal price for each unit of pollution. While Johnstone (2005) argues that the choice of regulatory strategy should be flexible and be able to adapt to changing market conditions, Johnstone, Haščič and Kalamova (2010) find evidence that less rigid innovation regulations based on taxes and tradable permits are more effective at inducing eco-innovation than strict performance standards or technology based controls. They also find evidence that any policy that sets a strict price for polluting incentivises firms to search for ways to avoid these costs and they find that any increase in that price induces further innovation (especially air, water and waste management innovation).…”
Section: Regulation As An Eco-innovation Drivermentioning
confidence: 97%
“…While there is growing pressure to deliver products and services which are environmentally friendly regulators and policy makers are faced with two market failures; (1) most environmental problems are negative externalities and (2) innovation is a positive externality. As a result firms harm the environment too much and innovate too little (Johnstone, Haščič and Kalamova 2010). Consequently while researchers examining the broad field of innovation comment on the importance of technology push (supply side) and market pull (demand side) drivers (Åstebro and Dahlin 2005), those focusing on eco-innovation stress the additional importance of regulation, environmental policy, institutional and political drivers (Horbach 2008;Horbach and Rennings 2007;Rehfeld, Rennings, and Ziegler 2007;Hemmelskamp 1999).…”
Section: Eco-innovation Driversmentioning
confidence: 99%
“…In particular, several studies (cf. Johnstone et al, 2010a;Rogge et al, 2011;Yin and Powers, 2010) discuss the influence of stringency (how difficult or expensive it is for market actors to comply) and predictability (how certain and foreseeable the policy signal is). However, the literature has also recognized the difficulty of measuring and comparing such features across countries 5 Considering that economic instruments are also regulated, a more correct term would be "direct regulatory instruments" (cf.…”
Section: Policy Instrument Typologymentioning
confidence: 99%
“…Based on a data set that includes 17 countries Lanjouw and Mody (1996) also found a positive correlation between PACE and environmental innovation. However, the use of PACE as a measure for policy stringency in a cross-country study is questionable due to the heterogeneity in the definitions and sampling strategies (see Johnstone et al 2012Johnstone et al , p. 2161. To overcome this problem Johnstone et al (2012) used survey data.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of PACE as a measure for policy stringency in a cross-country study is questionable due to the heterogeneity in the definitions and sampling strategies (see Johnstone et al 2012Johnstone et al , p. 2161. To overcome this problem Johnstone et al (2012) used survey data. Based on this data they again found that environmental innovation is positively affected by environmental policy stringency.…”
Section: Introductionmentioning
confidence: 99%